Climate Change, Gender, and Mental Health: African Eco-psychological Perspective - Paul Leshota; Makamohelo Pea Malimabe (Pharos Journal of Theology)
Global climate has changed over time, resulting in the change of precipitation patterns due to greenhouse emissions from fossil fuels. The devastating effects of the resulting global warming and climate change are pervasive. Both the earth and all that lives in it have become the victims of human’ obsession with ‘power over’, profit and greed. Middle and low-income countries are more on the receiving end of these adverse effects of global warming than the high-income countries who happen to be on the giving end of the emissions. While the environmental, physical, social, and structural effects of this change have been researched and documented, there has been comparatively little research about how climate change and mental health intersect to affect the relationship between human health and the entire ecological system. It is therefore the thrust of this paper to pursue this nexus with the view to delineate the extent to which climate change intersects with mental health, particularly in low income countries, to widen the inequality and vulnerability gap between peoples and countries. Even then, some groups – more than others – tend to become more vulnerable to mental health conditions than others. And these are more often than not, given inadequate or no attention as they are either concealed in the broader space of health services in general or under emergencies and disaster contexts. This desk top study adopts an African eco psychological framework within the context of Goal # 3 of the Sustainable Development Goals to underscore the importance of socio-cultural considerations in mitigating the impact of climate change on mental health.